The effect of corporate governance on the financial structure of listed firms - J. Augusto Felício; Ricardo Rodrigues (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
The purpose of this study is to analyse the influence of corporate governance on the financial structure of listed firms. The analysis is founded on the capital structure and agency theories. Corporate governance literature indicates the existence of nonlinear relationships, and hence this research applies multiple linear regression to a sample of 100 firms listed on the London Stock Exchange, corresponding to a 3-year period. The results confirm the influence of corporate governance on the financial structure of listed firms, and in particular, the nonlinear effect of the percentage of executive members of the board.
Keywords: 650; Corporate governance; financial structure; agency theory; listed firms